2006
DOI: 10.1677/joe.1.06661
|View full text |Cite
|
Sign up to set email alerts
|

Selenium treatment in autoimmune thyroiditis: 9-month follow-up with variable doses

Abstract: The aim of this study is to investigate the long-term (9 months) effects of variable doses (200/100 mg/day) of L-selenomethionine on autoimmune thyroiditis (AIT) and the parameters affecting the success rate of this therapy. The present study was designed in three steps: (1) 88 female patients with AIT (mean ageZ40$1G13$3 years) were randomized into two groups according to their initial serum TSH, thyroid peroxidase antibody (TPOAb) concentrations, and age. All the patients were receiving L-thyroxine to keep s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 21 publications
12
90
1
9
Order By: Relevance
“…However, the interaction is modest when subjects are not sufficiently iodine and/or selenium deficient (16,19). Beneficial effects of selenium supplementation on autoimmune thyroiditis have been reported, possibly through the action of GPx in enhancing the immune system and protecting the thyroid gland against oxidant stress (30)(31)(32). In a recent randomized controlled trial with patients with autoimmune thyroiditis, physiological doses of selenium improved thyroid structure and reduced autoantibody titer (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction is modest when subjects are not sufficiently iodine and/or selenium deficient (16,19). Beneficial effects of selenium supplementation on autoimmune thyroiditis have been reported, possibly through the action of GPx in enhancing the immune system and protecting the thyroid gland against oxidant stress (30)(31)(32). In a recent randomized controlled trial with patients with autoimmune thyroiditis, physiological doses of selenium improved thyroid structure and reduced autoantibody titer (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has thus been hypothesized that even mild nutritional selenium deficiency may promote the initiation or progression of thyroid autoimmunity. To test the hypothesis that selenium supplementation decreases the serum concentration of TPO-Ab, six randomized clinical trials have been performed (55,56,57,58,59,60).…”
Section: Seleniummentioning
confidence: 99%
“…In addition, based on the data from two studies, the beneficial effect of selenium supplementation was confirmed regarding the mood of the patients [126]. Brief characteristics of the most important prospective clinical studies [98,122,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] concerning the efficacy of supplementation with selenium in benign thyroid diseases, in particular autoimmune diseases, are presented in Table II.…”
Section: ) Short Characteristics Of the Most Important Clinical Trimentioning
confidence: 99%